2021
DOI: 10.1007/s00401-021-02293-4
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal inflammation in multiple sclerosis induces phenotypic changes in cortical microglia that differentially associate with neurodegeneration

Abstract: Meningeal inflammation strongly associates with demyelination and neuronal loss in the underlying cortex of progressive MS patients, thereby contributing significantly to clinical disability. However, the pathological mechanisms of meningeal inflammation-induced cortical pathology are still largely elusive. By extensive analysis of cortical microglia in post-mortem progressive MS tissue, we identified cortical areas with two MS-specific microglial populations, termed MS1 and MS2 cortex. The microglial populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…While P2RY12 was significantly lower in cortical IBA1-positive microglia compared to controls. Interestingly, the other homeostatic marker—TMEM119—was not differentially expressed [ 97 ].…”
Section: Mhciimentioning
confidence: 99%
See 1 more Smart Citation
“…While P2RY12 was significantly lower in cortical IBA1-positive microglia compared to controls. Interestingly, the other homeostatic marker—TMEM119—was not differentially expressed [ 97 ].…”
Section: Mhciimentioning
confidence: 99%
“…However, Van Olst et al [ 97 ] demonstrated no increased expression of CD68 in multiple sclerosis, therefore emphasizing the importance of using several markers in order to describe the microglial phenotypes as thoroughly as possible.…”
Section: Cd68mentioning
confidence: 99%
“…Their processes dynamically surveil the brain microenvironment in healthy conditions ( Madry et al, 2018 ). Following injury or in disease, microglia display a strong reactive response in which they retract their processes, reduce expression of resting phenotype proteins (such as P2Y12R, Cx3CR1, and TMEM119), and take on the amoeboid morphology and phagocytic characteristics of tissue macrophages ( Lee et al, 2010 ; Salter and Stevens, 2017 ; van Olst et al, 2021 ). In this activated state, microglia can also release cytokines and other signaling molecules that induce reactive astrogliosis with a range of beneficial ( Fukumoto et al, 2019 ) or detrimental ( Liddelow et al, 2017 ) outcomes.…”
Section: Neurovascular Unit: Components and Developmentmentioning
confidence: 99%
“…MS 2 ↓ P2Y 12 R, hyper-ramified morphology [21] EAE animal model (early phase) Pro-inflammatory CD86, CD40, MHC-II [22] TNF-α, IFN-γ, IL-…”
Section: Initial and Early White Matter Active Lesionsmentioning
confidence: 99%